Comparison of prophylactic topical application of Cryptomphalus aspersa secretion versus betamethasone for telecobalt radiation-induced skin reactions in locally advanced head and neck carcinoma patients - Ramashish Kumar; Ashok Chauhan; Sovan Sarang Dhar; Nitish Kumar (Asian Journal of Medical Sciences)
Background: External beam radiation therapy (EBRT) with or without concurrent chemotherapy is practiced as backbone of treatment across sites and subsites of head and neck cancer (HNC) when the intent is definitive. Radiation-induced acute skin reaction is of major concern during and after definitive course of radiotherapy. Prevention and treatment of these reactions play an important role in the completion of the prescribed course of EBRT within stipulated time period while maintaining the quality of life.